Comportamiento espacial y temporal de Thrips simplex Morison (Thysanoptera: Thripidae) en la región norte del Estado de México - Quiñones-Valdez, Rosalba; Sánchez-Pale, Jesús Ricardo; Castañeda-Vildozola, Álvaro; Franco Mora, Omar; Johansen-Naime, Roberto; Mejorada-Gómez, Elizabeth (Instituto de Ecología, A.C., 2020)
The gladiolus is the most widely cultivated ornamental in Mexico. Its flowers are commercialized year-round, though demand is particularly high on specific dates, such as Father's Day and Day of the Dead. Principal phytosanitary problems include trips, whitefly, rust, and drying. Trips are considered the main insect pest due to the extensive damage they cause to flower quality, leading to economic loss in addition to the already high investment in their control. The objective of this work was to determine the spatial and temporal behavior of Thrips simplex (Morison, 1930) in commercial plots of roja borrega variety gladiolus. Thrip density was evaluated using 121 yellow-colored traps during three phenological stages in each of the two plots evaluated, during the winter-spring and summer-fall growing cycles of 2013 and 2014. Traps were georeferenced and placed according on a 10m x 10m grid in each plot. A geostatistical analysis was carried out to obtain the experimental semivariograms for adjusted theoretical models and generate density maps. Thrips simplex was found to be present throughout all stages of the gladiolus phenological cycle in both years of the study, and showed an aggregated spatial and temporal behavior, adjusted to different spatial patterns. Densities varied little among sampling dates, though the location and dispersal of aggregation centers differed among the three phenological stages in each plot, when visualized using the maps generated in the two production cycles evaluated.